"We are all patrons" : how artists receive patronage in support of their work for the common good - Bonkovsky, Erik (St. Louis, Missouri : Covenant Theological Seminary, 2017)
1 online resource (PDF (vii, 146 leaves)); Abstract; Thesis (D. Min.)--Covenant Theological Seminary, 2017; Bibliography: leaves 141-146